APAKAH FAKTOR SOSIOEKONOMI MEMPENGARUHI KEMAUAN MEMBAYAR RETRIBUSI PELAYANAN SAMPAH? : STUDI KASUS KOTA TANGERANG SELATAN - Dhian Adhetiya Safitra (Polytechnic of State Finance STAN, 2024)
Population growth differs from the increase in waste generation. A case study conducted in South Tangerang City found that levies can serve as an economic tool to influence behavior and finance waste management. This study identifies the factors that affect residents’ willingness to pay these levies, which local governments can utilize to develop tariff imposition strategies. Using ordinary least squares analysis, the study revealed that income level and housing type (complex or non-complex) significantly impact the willingness to pay. Based on these findings, South Tangerang City can differentiate levy rates between various housing types according to residents' income levels.